Academic freedom: Global variations in norm conceptualization, diffusion and contestation – an introduction - Kriszta Kovács; Janika Spannagel (Global Constitutionalism, 2024)
This Introduction provides an overview of the topics covered in this special issue on `Academic freedom: Global variations in norm conceptualization, diffusion and contestation', which explores what academic freedom means, how this may vary on a global level, how the norm spread around the world and what current contestations look like. The Introduction defines some terms essential to this debate, such as the freedom of science, academic freedom, freedom of scientific research and the right to science, and offers an analytical framework for the various contributions of the special issue. This includes, in particular, a distinction between illiberal and liberal science scripts and their relationship with academic freedom, as well as between different forms of contestations and limitations of academic freedom. Authors from varying disciplinary and regional backgrounds address different aspects of this theme in their respective contributions, of which the introduction gives a brief summary.
Keywords: 300; academic freedom; contestations; freedom of science; limitations; science script